Extinction of Fear Memory Attenuates Conditioned Cardiovascular Fear Reactivity - Swiercz, Adam P.; Seligowski, Antonia V.; Park, Jeanie; Marvar, Paul J. (Frontiers in Behavioral Neuroscience, 2018)
Post-traumatic stress disorder (PTSD) is characterized by a heightened emotional and physiological state and an impaired ability to suppress or extinguish traumatic fear memories. Exaggerated physiological responses may contribute to increased cardiovascular disease risk in this population, but whether treatment for PTSD can offset cardiovascular disease risk remains unknown. To further evaluate physiological correlates of fear learning, we used a novel pre-clinical conditioned cardiovascular testing paradigm and examined the effects of Pavlovian fear conditioning and extinction training on mean arterial pressure (MAP) and heart rate (HR) responses. We hypothesized that a fear conditioned cardiovascular response could be detected in a novel context and attenuated by extinction training. In a novel context, fear conditioned mice exhibited marginal increases in MAP (~3 mmHg) and decreases in HR (~20 bpm) during CS presentation. In a home cage context, the CS elicited significant increases in both HR (100 bpm) and MAP (20 mmHg). Following extinction training, the MAP response was suppressed while CS-dependent HR responses were variable. These pre-clinical data suggest that extinction learning attenuates the acute MAP responses to conditioned stimuli over time, and that MAP and HR responses may extinguish at different rates. These results suggest that in mouse models of fear learning, conditioned cardiovascular responses are modified by extinction training. Understanding these processes in pre-clinical disease models and in humans with PTSD may be important for identifying interventions that facilitate fear extinction and attenuate hyper-physiological responses, potentially leading to improvements in the efficacy of exposure therapy and PTSD-cardiovascular disease comorbidity outcomes.